(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Despite the variety of etiological factors, mechanisms of development of allergic dermatoses, as well as huge clinical differences in localization, morphology of rashes, subjective complaints of the patient, a number of immunological changes are the basis for the implementation of inflammation in the skin. Approaches to the treatment of these diseases are determined by their etiological and pathogenetic mechanisms of development and consist in carrying out elimination measures, the use of both systemic and external pharmacotherapy.